Effect of Nanodiamond Addition on Flexural Strength, Impact Strength, and Surface Roughness of PMMA Denture Base. Issue 1 (23rd October 2018) - Al‐Harbi, Fahad A.; Abdel‐Halim, Mohamed S.; Gad, Mohammed M.; Fouda, Shaimaa M.; Baba, Nadim Z.; AlRumaih, Hamad S.; Akhtar, Sultan
Abstract: Purpose: To assess the effect of addition of different concentrations of nanodiamonds (NDs) on flexural strength, impact strength, and surface roughness of heat‐polymerized acrylic resin. Materials and Methods: 120 specimens were fabricated from heat‐polymerized acrylic resin. They were divided into a control group of pure polymethylmethacrylate (PMMA; Major.Base.20) and three tested groups (PMMA‐ND) with 0.5%wt, 1%wt, and 1.5%wt of added ND to PMMA. Flexural strength was determined using the three‐point bending test. Impact strength was recorded by using a Charpy type impact test. Surface roughness test was performed using a Contour GT machine. One‐way ANOVA and Tukey's post‐hoc analysis ( p ≤ 0.05) were used for statistical analysis. Results: Acrylic resin reinforced with 0.5% ND displayed significantly higher flexural strength than the unreinforced heat‐polymerized specimens, acrylic resin reinforced with 1% ND and the 1.5% ND ( p < 0.0001). The impact strength of unreinforced heat‐polymerized specimens was significantly higher than all nano‐composite materials ( p < 0.0001) with no significant difference between 1% ND and the 1.5% ND ( p > 0.05). The addition of 0.5% ND and 1% ND significantly decreased the surface roughness in comparison to both control and the 1.5% ND groups ( p < 0.0001) while no significant differences between 0.5% ND and 1% ND ( p > 0.05) were reported. Nano‐composite material (0.5% ND) showed significantly lower surface roughness when compared to other specimens. Conclusions: The addition of NDs to acrylic denture base improved the flexural strength and surface roughness at low concentrations (0.5%), while the impact strength was decreased with ND addition.